TO90 inhibits angiotensin II-induced inflammatory response by up-regulating ACE2/Ang-(1-7)/MAS receptor axis in human retinal pigment epithelial cells - MAI Yuxin; WANG Luoziyi; YU Peng; LIU Yanyao; LEI Bo (Di-san junyi daxue xuebao, 2019)
Objective To investigate whether TO90 inhibits angiotensin II (Ang Ⅱ)-induced inflammatory response by regulating the expressions of ACE2/Ang-(1-7)/MAS receptor axis in human retinal pigment epithelial cells. Methods In vitro cultured ARPE-19 cells were treated with Ang Ⅱ for 48 h, and the changes in the expressions of interleukin-6 (IL-6), IL-8 and monocyte chemoattractant protein-1 (MCP-1) were detected using real-time PCR and enzyme-linked immunosorbent assay (ELISA) to verify the establishment of the inflammatory cell model. The effect of TO90 on the inflammatory response of Ang Ⅱ-treated ARPE-19 cells was evaluated by detecting the expression of IL-6, IL-8, MCP-1, ACE2 and MAS receptor using real-time PCR and Western blotting. ARPE-19 cells treated with Ang Ⅱ, TO90+Ang Ⅱ, A779 (a MAS receptor inhibitor)+TO90+Ang Ⅱ, or A779+Ang Ⅱ were examined for expressions of IL-6, IL-8, MCP-1, ACE2 and MAS receptors to further explore the effect of TO90 on Ang Ⅱ-induced inflammation response. Results Ang Ⅱ treatment resulted in significantly increased expressions of IL-6, IL-8 and MCP-1 at both the mRNA and protein levels in ARPE-19 cells (P < 0.05), and these effects were obviously attenuated by pretreatment of the cells with TO90 (P < 0.05), which also caused significantly increased expressions of ACE2 and MAS receptor in the cells (P < 0.05). In ARPE-19 cells treated with TO90+Ang Ⅱ, inhibition of MAS receptor with A779 significantly enhanced the expression of IL-6, IL-8, MCP-1, while inhibited the expression of ACE2 and MAS receptor at both the mRNA and protein levels (P < 0.05). Conclusion TO90 inhibits Ang II-induced inflammatory response by up-regulating the expressions of ACE2/Ang-(1-7)/MAS receptor axis in ARPE-19 cells.